If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -9 + 15 = 2x + 10 Reorder the terms: -9 + 15 + 3x = 2x + 10 Combine like terms: -9 + 15 = 6 6 + 3x = 2x + 10 Reorder the terms: 6 + 3x = 10 + 2x Solving 6 + 3x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6 + 3x + -2x = 10 + 2x + -2x Combine like terms: 3x + -2x = 1x 6 + 1x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 6 + 1x = 10 + 0 6 + 1x = 10 Add '-6' to each side of the equation. 6 + -6 + 1x = 10 + -6 Combine like terms: 6 + -6 = 0 0 + 1x = 10 + -6 1x = 10 + -6 Combine like terms: 10 + -6 = 4 1x = 4 Divide each side by '1'. x = 4 Simplifying x = 4
| f(x+4)=6x-7 | | -y+148=274 | | -w+266=151 | | L=100w | | 25x-30x=5-10 | | x=100y | | 162=229-w | | h(t)=16t^2+65t+3.5 | | -0.65x^3+0.57x^2+56.68x+3104= | | x-3/4x-3=4 | | (y^2+y)-7(4y^2-5y)+2= | | x^2+bx+15=0 | | (-2x+8)=0 | | (3x+6)=6 | | (-2-x)=9 | | (x)=-0.65x^3+0.57x^2+56.68x+3104 | | (4x-2)=-6 | | 3.5(6x-2)=3.5 | | 5(-3.1x+6.9)=-3.5 | | 5z=2.3+4.2 | | x*20/3=5/6 | | -0.3(3+8x)=0.9 | | -3(2x+1.2)=-1 | | 12/19=-4z | | 0=-0.5x^2+7x-20 | | 8x+82x=80 | | 9=3y+37+4y | | 5/2t=-7/3 | | x=-0.5x^2+7x-20 | | -12x^2+42x-20=0 | | -(2x-10)-1=2 | | 3a^2+27b^2+5c^2-18ab-30c=-237 |